2013
DOI: 10.1248/cpb.c13-00404
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Chemistry and Chemical Biology of Diketopiperazine-Type Antimicrotubule and Vascular-Disrupting Agents

Abstract: Certain antimicrotubule agents displaying colchicine-like tubulin-depolymerizing activity can act as both cytotoxic and vascular-disrupting agents (VDAs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…For example, diketopiperazines have found therapeutic application in the treatment of erectile dysfunction as inhibitors of phosphodiesterase-5 [11], as well as antagonists of oxytocin for the treatment of preterm labor [12]. Another significant example is the vascular disrupting and tubulin-depolymerizing agent plinabulin, based on the marine fungal agent halimide, and currently on the last stage of clinical development for the treatment of non-small-cell lung cancer (NSCLC) [13,14,15]. The diketopiperazine-derived template has been also investigated as a brain shuttle for the delivery of medicinal agents with limited ability to cross the blood-brain barrier, bypassing the limited bioavailability of several drugs [16,17].…”
Section: General Considerationsmentioning
confidence: 99%
“…For example, diketopiperazines have found therapeutic application in the treatment of erectile dysfunction as inhibitors of phosphodiesterase-5 [11], as well as antagonists of oxytocin for the treatment of preterm labor [12]. Another significant example is the vascular disrupting and tubulin-depolymerizing agent plinabulin, based on the marine fungal agent halimide, and currently on the last stage of clinical development for the treatment of non-small-cell lung cancer (NSCLC) [13,14,15]. The diketopiperazine-derived template has been also investigated as a brain shuttle for the delivery of medicinal agents with limited ability to cross the blood-brain barrier, bypassing the limited bioavailability of several drugs [16,17].…”
Section: General Considerationsmentioning
confidence: 99%
“…A large number of analogs of this lead compound have been prepared with a view to improve its potency and aqueous solubility. 48 Plinabulin derivatives probably do not interact with the colchicine binding site. Instead, they interact with the boundary region between the α-and β-tubulins around the colchicine site.…”
Section: Compounds Binding At the Colchicine Sitementioning
confidence: 99%
“…This compound, a simple modification of the terrestrial and also marine fungal metabolite halimide [88], entered Phase II clinical trials under Nereus Pharmaceuticals (San Diego, CA, USA). Two completed trials under that sponsor are shown in the NIH database, one at Phase I and the other at Phase I/II.…”
Section: Other Marine-derived Compounds In Clinical Trials Againstmentioning
confidence: 99%